Trained Immunity Enhances Human Monocyte Function in Aging and Sepsis - Gill, P. Spencer; Ozment, Tammy R.; Lewis, Nicole H.; Sherwood, Edward R.; Williams, David L. (Frontiers in Immunology, 2022)
Aging plays a critical role in the incidence and severity of infection, with age emerging as an independent predictor of mortality in sepsis. Trained immunity reprograms immunocytes to respond more rapidly and effectively to pathogens and serves as a potential approach to improve immune function in aging and/or sepsis. However, there is very little data on trained immunity in the aging immune system or in the presence of sepsis. We examined the impact of -glucan induced innate immune training on monocytes from aging healthy humans (>60 years old) as well as sepsis patients. We observed increased metabolic capacity, upregulated cytokine secretion, increased H3K27 acetylation, and upregulation of crucial intracellular signaling pathways in trained monocytes from healthy aging subjects. The response to trained immunity in healthy aging monocytes was equivalent to the response of monocytes from younger, i.e., 18 – 59 years, individuals. Additionally, we found that trained immunity induced a unique expression pattern of cell surface markers in monocytes that was consistent across age groups. Trained monocytes from sepsis patients also displayed enhanced metabolic capacity and increased cytokine production. These results indicate that immune training can be induced in aging monocytes as well as monocytes from critically ill sepsis patients.